PENGARUH LOGISTICS SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION PADA PENGGUNA JASA KURIR SHOPEE EXPRESS DI SURABAYA - Siska Anggreani; Stefanus Budy Widjaja Subali; Fitri Novika Widjaja (CALYPTRA, 2024)
Abstract—This study aims to determine the effect of logistics service quality, namely personnel contact quality, timeliness, order conditions, order discrepancy handling, and operational information sharing on customer satisfaction among Shopee Express courier service users in Surabaya. This research method uses a questionnaire with a total of 180 respondents in Surabaya who have used Shopee Express in the last 6 months. The regression model in this study is SEM (Structural Equation Model) with AMOS 23 software. The results of this study indicate that the variables of personnel contact quality, timeliness, order condition, order discrepancy handling, and operational information sharing have an effect on customer satisfaction. Keywords: logistics service quality, customer satisfaction, shopee express Abstrak—Penelitian ini bertujuan untuk mengetahui pengaruh logistics service quality, yaitu personnel contact quality, timeliness, order condition, order discrepancy handling, dan operational information sharing terhadap customer satisfaction pada pengguna jasa kurir Shopee Express di Surabaya. Metode penelitian ini menggunakan kuesioner dengan jumlah responden sebesar 180 responden di Surabaya yang pernah menggunakan Shopee Express 6 bulan terakhir. Model pada penelitian merupakan SEM (Structural Equation Model) dengan software AMOS 23. Hasil penelitian ini menunjukkan bahwa variabel personnel contact quality, timeliness, order condition, order discrepancy handling, dan operational information sharing berpengaruh terhadap customer satisfaction. Kata kunci: kualitas layanan logistik, kepuasan pelanggan, shopee express